One good turn : a jolly murder mystery - Atkinson, Kate.; Black Swan. (London : Black Swan, 2007)
While waiting outside a theater with dozens of other fans, ex-private detective and recent millionaire Jackson Brodie witnesses a shocking act of road rage that thrusts him into a world of corruption, violence, and danger that threatens his riches and his life.
Adult
Keywords: Millionaires -- Fiction; Policewomen -- Fiction; Women novelists -- Fiction; Edinburgh (Scotland) -- Fiction